2019
DOI: 10.1136/annrheumdis-2018-214894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of tocilizumab monotherapy and adalimumab in combination with methotrexate on bone erosion repair in rheumatoid arthritis

Abstract: ObjectiveTo compare the effects of interleukin-6 (IL-6) receptor and tumour necrosis factor inhibition on inducing repair of existing bone erosions in patients with very early rheumatoid arthritis (RA).MethodsProspective non-randomised observational study in patients with active erosive RA with inadequate response to methotrexate (MTX) receiving either tocilizumab (TOC) monotherapy or adalimumab (ADA) with MTX for 52 weeks. Erosion volumes were assessed in metacarpal heads (MCH) and the radius by high-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
0
36
1
1
Order By: Relevance
“…On the basis of these results, EULAR recommendations for the management of RA named IL-6 pathway inhibitors as one of the preferred treatment options for patients for whom methotrexate is inappropriate 60 . Interestingly, the clinical benefits of IL-6 inhibition might be attributable, in part, to the beneficial effects of IL-6 inhibition on bone and cartilage turnover, which are supported by data from prospective cohort studies showing that tocilizumab monotherapy achieves better repair of focal bone erosions than TNF inhibition in patients with RA [60][61][62][63][64][65][66][67][68][69][70] . Besides promoting joint inflammation and damage through effects on chondrocytes, osteoclasts, macrophages and fibroblasts, IL-6 mediates systemic inflammation in RA.…”
Section: Il-6 Inhibition In Ramentioning
confidence: 99%
“…On the basis of these results, EULAR recommendations for the management of RA named IL-6 pathway inhibitors as one of the preferred treatment options for patients for whom methotrexate is inappropriate 60 . Interestingly, the clinical benefits of IL-6 inhibition might be attributable, in part, to the beneficial effects of IL-6 inhibition on bone and cartilage turnover, which are supported by data from prospective cohort studies showing that tocilizumab monotherapy achieves better repair of focal bone erosions than TNF inhibition in patients with RA [60][61][62][63][64][65][66][67][68][69][70] . Besides promoting joint inflammation and damage through effects on chondrocytes, osteoclasts, macrophages and fibroblasts, IL-6 mediates systemic inflammation in RA.…”
Section: Il-6 Inhibition In Ramentioning
confidence: 99%
“…Conversely, erosion volume increased significantly in patients receiving alendronate, while decreasing significantly in patients receiving denosumab after 6 months. While these represent the shortest time interval over which changes in erosion volume and JSW have been observed, two studies have shown decreases in erosion volume in response to tocilizumab in combination with methotrexate for both patients with newly diagnosed RA (59) and established RA (15); this has also been observed for patients with established RA treated with TNFi in combination with methotrexate (6) over a 1-year follow-up. Stabilization in erosion size with therapy has also been demonstrated, in newly diagnosed patients with RA on treatment with a TNFi in combination with methotrexate (59).…”
Section: Longitudinal Changes Of the Pathological Measuresmentioning
confidence: 95%
“…Fifteen studies have reported longitudinal changes in the number and/or size of erosions. Of these, three investigated PsA (14,49,66), 10 investigated patients with RA (6,10,15,29,42,46,58,59,64,65), and one study examined ACPA+ individuals without arthritis (62). Seven studies investigated intervention with different therapies either as an open-label study or secondary analysis in a randomized controlled trial.…”
Section: Longitudinal Changes Of the Pathological Measuresmentioning
confidence: 99%
“…However, therapies involving MTX often have inadequate response or intolerance, which calls for alternative treatments such as biological agents [6]. One of them is Tocilizumab (TCZ), a humanized anti-IL-6 receptor monoclonal antibody, which acts by blocking IL-6 signaling [7][8][9]. Elevated levels of IL-6 in synovial uid and serum correlate with disease activity in patients with RA [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of IL-6 in synovial uid and serum correlate with disease activity in patients with RA [10][11]. Inhibition of the IL-6 signaling by TCZ showed a protective effect on bone erosions by decreasing their volume in RA patients and signi cant reduction of swollen and tender joint counts with concurrent improvement in radiographic progression [12] [9].…”
Section: Introductionmentioning
confidence: 99%